Characteristics of Neural Network Changes in Normal Aging and Early Dementia - Watanabe, Hirohisa; Bagarinao, Epifanio; Maesawa, Satoshi; Hara, Kazuhiro; Kawabata, Kazuya; Ogura, Aya; Ohdake, Reiko; Shima, Sayuri; Mizutani, Yasuaki; Ueda, Akihiro; Ito, Mizuki; Katsuno, Masahisa; et al. (Frontiers in Aging Neuroscience, 2021)
To understand the mechanisms underlying preserved and impaired cognitive function in healthy aging and dementia, respectively, the spatial relationships of brain networks and mechanisms of their resilience should be understood. The hub regions of the brain, such as the multisensory integration and default mode networks, are critical for within- and between-network communication, remain well-preserved during aging, and play an essential role in compensatory processes. On the other hand, these brain hubs are the preferred sites for lesions in neurodegenerative dementias, such as Alzheimer's disease. Disrupted primary information processing networks, such as the auditory, visual, and sensorimotor networks, may lead to overactivity of the multisensory integration networks and accumulation of pathological proteins that cause dementia. The brain hub regions contain many synapses and require a large amount of energy. This region is rich in ATP-related gene expression, and had high glucose metabolism demonstrated on PET. Importantly, the number and function of mitochondria, which are the center of ATP production, decline by about 8% every 10 years. Dementia patients often have dysfunction of the ubiquitin-proteasome and autophagy-lysosome systems, which require large amounts of ATP. If there is low energy supply and high demand, the risk of disease is high. Imbalance between energy supply and demand may cause accumulation of pathological proteins and play an important role in the development of dementia. This energy imbalance explains why brain hub regions are vulnerable to damage in different dementias.